2023
DOI: 10.1186/s12885-023-10585-z
|View full text |Cite
|
Sign up to set email alerts
|

Mean platelet volume/platelet count ratio in combination with tumor markers in colorectal cancer: a retrospective clinical study

Abstract: Background Mean platelet volume (MPV) is a marker of platelet activation, which is usually negatively correlated with platelet count (PC). The ratio of MPV to PC (MPV/PC) has an essential role in the diagnosis of multiple malignancies. However, only a few studies investigated the value of MPV/PC in colorectal cancer (CRC) and the combination of MPV/PC with tumor markers in CRC. This retrospective clinical study aimed to evaluate the diagnostic value of MPV/PC and tumor markers (CA72-4, CA125, C… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 34 publications
0
4
0
Order By: Relevance
“…According to previous research, MPR combined with tumor markers has already been applied in the differential diagnosis of benign and malignant lesions. Zhang et al combined MPR with CA125, CA724 and CA19-9, and confirmed that MPR combined with tumor markers could better distinguish colorectal cancer from colorectal polyps than MPR alone, and that this combination was also able to predict the differentiation, nerve invasion and vascular invasion of colorectal cancer [32]. Therefore, we introduced a combined index of MPR and CA19-9.…”
Section: Discussionmentioning
confidence: 59%
“…According to previous research, MPR combined with tumor markers has already been applied in the differential diagnosis of benign and malignant lesions. Zhang et al combined MPR with CA125, CA724 and CA19-9, and confirmed that MPR combined with tumor markers could better distinguish colorectal cancer from colorectal polyps than MPR alone, and that this combination was also able to predict the differentiation, nerve invasion and vascular invasion of colorectal cancer [32]. Therefore, we introduced a combined index of MPR and CA19-9.…”
Section: Discussionmentioning
confidence: 59%
“… 59 MPV/TPC was associated with tumor infiltration and regional lymph node metastasis in CRC. 53 TPC/PLR was associated with depth of infiltration, 60 and this infiltration was associated with poor prognosis in postsurgical CRC patients. 61 Nowadays, some prediction models, like the ColonFlag model, have been introduced that use blood-based parameters (including PLC), age and sex combined with machine-learning techniques to differentiate high-risk from low-risk CRC patients.…”
Section: Cancer and Plateletsmentioning
confidence: 88%
“… 52 Other studies showed that CRC patients, compared to the adenomatous polyp group, have higher MPV levels. 53 , 54 Qian et alreported that in non-metastatic CRC, the pre- and post-treatment ratio of MPV is a prognostic factor for overall survival. 55 Despite the contradictory findings of the MPV levels in cancer cases and healthy individuals, it is agreed by the majority of researches that reduced MPV is a good prognostic biomarker for cancer cases.…”
Section: Cancer and Plateletsmentioning
confidence: 99%
See 1 more Smart Citation